Pengaruh Strategi Penangkapan Ikan Ramah Lingkungan di Pantai Olo, Kecamatan Belawan - Meilinda Suriani Harefa; Elsa Kardiana; Angel Lena Simanjuntak; Yordan Sihotang; Sogya Solin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the impact of environmentally friendly fishing strategies implemented by local fishermen on catch outcomes and the sustainability of marine ecosystems in Pantai Olo, Belawan District. In response to increasing ecological pressure caused by exploitative fishing practices, the adoption of more sustainable approaches has become essential. This research employs a qualitative approach with descriptive methods. Data were collected through field observations, in-depth interviews with fishermen, and literature review. The findings indicate that the use of selective fishing gear, such as appropriately sized nets, contributes to improved catch quality and the preservation of fish populations. Although daily catch volumes may be lower compared to conventional methods, fishermen reported long-term benefits, including income stability and resource availability. Nonetheless, limited access to appropriate technology and training remains a significant challenge. These findings highlight that environmentally friendly fishing strategies generate notable ecological and economic benefits, emphasizing the need for continuous policy support and capacity-building initiatives.